(untitled) (One Health & Risk Management, 2023)
Introduction. Introduction. Osteoporosis is a skeletal disease characterized by compromising the mechanical strength of the bone and increasing the risk of fractures. Osteoporosis conditions the increase in illness and disability in the elderly and, respectively, leads to an increase in health expenses. Material and methods. A cross-sectional descriptive epidemiological study was designed, which included surveying 423 respondents and interviewing representatives of health decision-makers (6 in-depth interviews), during 2020-2022. Results. In the section on knowledge about osteoporosis, a dissociation of responses was recorded according to the gender criterion – women in 65.4% of cases know better about this problem (χ2=3.898, p=0.273). Knowledge about the fact that osteoporosis can occur during menopause was demonstrated by 45.9% of respondents, of whom women in 76.3% of cases (χ2=36,136,183, p<0.001). The attitude of the respondents was analyzed according to the biological gender. It was found that women show concern about osteoporosis in 63.6% of cases, and men – 35.2%. In the practices chapter, it was found that the respondents consume little milk and cottage cheese, but they usually take calcium food supplements (54%). Conclusions. Osteoporosis is a current public health problem. Females possess more knowledge about osteoporosis and show a more expressive attitude compared to males.